PERBANDINGAN INDEKS ERITROSIT PADA PENDERITA TUBERKULOSIS YANG MENJALANI PENGOBATAN FASE AWAL DAN FASE LANJUTAN SEBAGAI MONITORING RISIKO ANEMIA - Yanti Sunaidi; Imelda pongsimpin; Nuramaniyah Taufiq (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2024)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Tuberculosis can be treated by taking Anti-Tuberculosis Drugs (OAT). Tuberculosis treatment is divided into two phases, namely the initial phase and the advanced phase. Side effects of OAT use can cause hematological abnormalities in the blood such as anemia. The purpose of this study was to determine the comparison of erythrocytes in tuberculosis patients undergoing initial and advanced phase treatment as monitoring of anemia risk. This type of research was a comparative study. The research subjects were 30 subjects undergoing initial phase treatment and 30 subjects in advanced phase treatment obtained using the total sampling method. The results of this study obtained a normal erythrocyte index in the early phase of 21 (70%) subjects, normocytic hypochromic 6 (20%) subjects, and microcytic hypochromic 3 (10%) subjects. In comparison, the normal erythrocyte index in the advanced phase was 26 (87%) subjects and microcytic hypochromic 4 (13%) subjects. From the results of the statistical test study using the Mann-Whitney test, the Asymp. Sig. (2 tailed) value was obtained 0.000 (<0.05), which indicates that there is a comparison between the results of the erythrocyte index examination in TB patients undergoing early and advanced phase treatment so that in this study, the hypothesis H is accepted and Ho is rejected. This study concludes that more people experience anemia in the early phase of treatment than in the advanced phase of treatment.